Chapter Risorse digitali per la didattica: una rassegna ragionata - Bellacci, Francesco (Public History of Education. Teorie, esperienze, strumenti, 2022)
The paper presents a reasoned review of digital resources useful for historians and the teaching of public history. This review will not be limited only to the tools of search and treatment of sources on the web, but will be directed above all to provide a guidance framework - which will be by the very nature of the digital constantly evolving over time - of those tools, methods and narratives that make use of digital to enhance teaching and research.